A Research of Chinese Companies' Cross-border Mergers & Acquisitions (M&A) Deal - LAI, XIAOXIAO (2008)
Economic market is getting more international and worldwide, to be globalization has become an irreversible trend for all the companies. The rise of globalization has exponentially added the number of cross-border mergers and acquisitions (M&A) deals. China's entrepreneurs realise that they have to establish their international strategic goals in order to be integrated into the world economic competition. Chinese companies are getting more and more deeply involved in the trend of cross-border M&A activities. However, many of Chinese companies still new to the concept and have limited experience and knowledge in operation cross-border M&A. These may be the reasons for the failure in the M&A deal. This dissertation is going to analysis how to enhance and improve the performance of future Chinese companies' cross-border M&A activities as well as to find out the necessary and essential issues which will have influence on the M&A innovation performance, so that to make future cross-border M&A more successfully.